Stability and Removal of Benzophenone-Type UV Filters from Water Matrices by Advanced Oxidation Processes - Belma Imamović; Polonca Trebše; Elma Omeragić; Ervina Bečić; Andrej Pečet; Mirza Dedić (Molecules, 2022)
Benzophenone (BP) type UV filters are common environmental contaminants that are posing a growing health concern due to their increasing presence in water. Different studies have evidenced the presence of benzophenones (BP, BP-1, BP-2, BP-3, BP-4, BP-9, HPB) in several environmental matrices, indicating that conventional technologies of water treatment are not able to remove them. It has also been reported that these compounds could be associated with endocrine-disrupting activities, genotoxicity, and reproductive toxicity. This review focuses on the degradation kinetics and mechanisms of benzophenone-type UV filters and their degradation products (DPs) under UV and solar irradiation and in UV-based advanced oxidation processes (AOPs) such as UV/H2O2, UV/persulfate, and the Fenton process. The effects of various operating parameters, such as UV irradiation including initial concentrations of H2O2, persulfate, and Fe2+, on the degradation of tested benzophenones from aqueous matrices, and conditions that allow higher degradation rates to be achieved are presented. Application of nanoparticles such as TiO2, PbO/TiO2, and Sb2O3/TiO2 for the photocatalytic degradation of benzophenone-type UV filters was included in this review.